Visualizing clogging up of soil pores in tropical degraded soils and their impact on green water productivity - Tebebu, Tigist Y.; Baver, C.; Stoof, C.; Steenhuis, Tammo S. (International Livestock Research Institute, 2013)
Restrictive soil layers commonly known as hardpans restrict water and airflow in the soil profile and impede plant root growth below the plough depth. Preventing hardpans to form or ameliorate existing hardpans will allow plants root more deeply, increase water infiltration and reduce runoff, all resulting in greater amounts of water available for the crop (i.e. green water). However, there has been a lack of research on understanding the influence of transported disturbed soil particles (colloids) from the surface to the subsurface to form restrictive soil layers, which is a common occurrence in degraded soils. In this study, we investigated the effect of disturbed soil particles on clogging up of soil pores to form hardpans. Unsaturated sand column experiments were performed by applying 0.04 g/ml soil water solution in two sand textures. For each experiment, soil water solution infiltration process was visualized using a bright field microscope and soil particles remained in the sand column was quantified collecting and measuring leachate at the end of the experiment in the soil and water lab of Cornell University. Preliminary results show that accumulation of significant amount of soil particles occur in between sand particles and at air water interfaces, indicating the clogging of soil pores occurs as a result of disturbed fine soil particles transported from the soil surface to the subsurface.